Effects of Drought on the Removal of Microplastics and other Environmental Pollutants from Urban Stormwater in Bioretention Filters - Friedrich, Michelle (My University, 2024)
Various particles and pollutants, such as microplastics, organic pollutants and nutrients, accumulate in untreated urban stormwater. In order to minimise surface water pollution from stormwater discharges, this study investigated the effects of drought on the removal efficiency of pollutants in bioretention filters with different sorption materials (waste-to-energy bottom ash, biochar, or sphagnum peat). The study was carried out in a rain garden pilot plant with 13 bioretention filters, 10 of them planted (armeria maritima, hippophae rhamnoides, juncus effusus and festuca rubra) and 3 unplanted. One planted bioretention filter of each sorption medium and one control filter were exposed to a dry period of 13 weeks. The remaining filters were regularly irrigated with the untreated stormwater runoff from the adjacent highway and the surrounding sealed surfaces. At the end of the dry period, all filter columns were irrigated, inflow and outflow water samples were taken and subsequently analysed for the previously mentioned pollutants in the laboratory. In general, high removal rates for microplastics >10μm, ions and nutrients were achieved in all filters. However, the drought had an impact on the removal efficiency with regard to TSS, VSS, TOC and DOC for all sorption media during the first irrigation and with increased pollutant concentrations in the inflow. In the course of the study, regeneration of all filters was observed, regardless of the sorption medium. Overall, it can be said that the different cleaning performance of the filters is primarily due to the different properties of the sorption materials and not the dry period. All sorption media contribute positively to the removal of pollutants. However, ash had the best cleaning performance in the overall comparison, therefore its implementation in rain gardens is recommended.